Tourists with Cameras: Reproducing or Producing? - Stylianou-Lambert, Theopisti (My University, 2012)
This paper examines tourists' photographic representations and processes in order to engage with the multidisciplinary literature that views tourists with cameras as either passive consumers of places or, alternatively, as active cultural producers. Specifically, this research examines tourists' photographic performances at the Rock of Aphrodite, the legendary birthplace of the Greek goddess in Cyprus, as well as whether or not tourists perpetuate, with their own photographs, images found on postcards. It is argued that even though tourists are active participants in the photographic process and produce photographs that have highly personal meanings, their photographs are still shaped by larger conventions such as the cultural construction of places, structural factors, sets of social and visual conventions as well as photographic etiquette
Keywords: Tourism--Research; Tourists; Heritage tourism; Tourism--Cyprus